Contestations of Citizenship, Education, and Democracy in an Era of Global Change: Children and Youth in Diverse International Contexts - Kubow, Patricia K (Critical Global Citizenship Education, 2022)
Contestations of Citizenship, Education, and Democracy in an Era of Global Change: Children and Youth in Diverse International Contexts considers the shifting social, political, economic, and educational structures shaping contemporary experiences, understandings, and practices of citizenship among children and youth in diverse international contexts. As such, this edited book examines the meaning of citizenship in an era defined by monumental global change. Chapters from across both the Global South and North consider emerging formations of citizenship and citizen identities among children and youth in formal and non-formal education contexts, as well as the social and civic imaginaries and practices to which children and youth engage, both in and outside of schools. Rich empirical contributions from an international team of contributors call attention to the social, political, economic, and educational structures shaping the ways young people view citizenship and highlight the social and political agency of children and youth amid increasing issues of polarization, climate change, conflict, migration, extremism, and authoritarianism. The book ultimately identifies emergent forms of citizenship developing in formal and non-formal educational contexts, including those that unsettle the nation-state and democracy. Edited by a team of academics with backgrounds in education, citizenship, and youth studies, this book will appeal to scholars, researchers, and faculty who work across the broader field of youth civic engagement and democracy, as well as international and comparative education and citizenship. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.